REVISITING THE SPIRIT OF RELIGIOUS NATIONALISM IN THE ERA OF PLURALISM AND GLOBALIZATION: Reading the Text of NDP of HMI - Makin, Al (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
This article is a reflection of the text of NDP (Nilai Dasar Perjuangan/Basic Principles of Struggle) text held by HMI (Himpunan Mahasiswa Islam/Muslim Student Association) as a basis of their activism struggle in Indonesia. The text consists of eight sections covering many aspects, such as theology, anthropology, sociology, and epistemology. By critical thinking, the NDP text of HMI should be transformed continuously toward an era of global diversity and plurality. In Indonesian context, there has been a fundamental change along with the democratization that brings out an openness and multi-party political system. This is important regarding that the NDP of HMI has been drafted in 1960 and 1970 when Nurcholis Madjid era faced the context of socio-political thought. The study found that the NDP of HMI is required to be changed in the context of new world order. It is not a sacred text, so the change is a necessity. *** Artikel ini merupakan refleksi dari teks NDP (Nilai Dasar Perjuangan) yang dimiliki HMI (Himpunan Mahasiswa Islam) sebagai dasar untuk perjuangan aktivisme mereka di Indonesia. Teks terdiri dari delapan bagian yang meliputi banyak aspek, mulai dari teologi, antropologi, sosiologi, hingga epistemologi. Dengan pembacaan secara kritis terhadap teks NDP HMI di tengah perubahan dunia global yang terus mengalami transformasi menuju era keragaman dan kemajemukan global. Pada konteks lokal Indonesia, juga telah terjadi perubahan yang mendasar seiring dengan gelombang demokratisasi yang memunculkan era keterbukaan dan sistem politik multipartai. Hal ini penting, mengingat NDP HMI disusun dalam kurun waktu antara tahun 1960 hingga 1970-an di mana era Nurcholis Madjid menghadapi konteks pemikiran dan sosial-politik pada waktu itu. Studi ini menemukan bahwa NDP HMI sudah sewajarnya memerlukan perubahan di tengah konteks dan tatanan dunia yang baru. NDP HMI bukanlah teks yang suci, sehingga perubahan adalah sebuah keniscayaan.